APPLICATION OF TECHNOLOGY AUGMENTED REALITY IN BROCHURES SMK GHAMA CARAKA DEPOK BASED ANDROID - Indarti Indarti; Dewi Laraswati (Jurnal Riset Informatika, 2020)
The brochure is one of the important instruments in terms of promotion to provide initial information for prospective students, but the brochure currently used is still fairly classic. Still using brochure leaflets on paper media and the information conveyed depends on the size of the printed brochure. If the school committee wants to provide more information by adding lots of pictures with product details, the larger the size of the brochure that needs to be printed. Research conducted using the concept of augmented reality in making interactive brochures based on Android. The steps involved consist of analyzing the software and hardware requirements to be used. The research method uses the case study method, with a qualitative approach. As for the application development model using the waterfall model which is a method in SDLC, the sequence of steps used in this research is system requirement analysis, design, program code making, testing and support